2019
DOI: 10.1177/0886260519884679
|View full text |Cite
|
Sign up to set email alerts
|

From Bully Victimization to Aggressive Behavior: Applying the Problem Behavior Theory, Theory of Stress and Coping, and General Strain Theory to Explore Potential Pathways

Abstract: Studies have documented that some bully victims fall into a subcategory of bullying called “bully victims” in which the victim becomes the aggressor. However, studies to date have not examined the pathways linking bully victimization and aggressive behavior. To address this research gap, this study applies the problem behavior theory, theory of stress and coping, and general strain theory to explore possible pathways from bully victimization to aggressive behavior by examining the mediating effects of low life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 63 publications
5
23
1
Order By: Relevance
“…Participants who witnessed civil speech were 1.5 times more likely to report uncivil participation, but those who had noted hate speech were nearly three times as likely to report engaging in uncivil behaviour online. In line with prior research on bullying (Lee et al, 2019) and studies on the toxic effects of having been victimised (Davis et al, 2020), the participants who had been personally victimised were 3.4 times as likely to report uncivil participation (H8) compared to those without such experiences.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Participants who witnessed civil speech were 1.5 times more likely to report uncivil participation, but those who had noted hate speech were nearly three times as likely to report engaging in uncivil behaviour online. In line with prior research on bullying (Lee et al, 2019) and studies on the toxic effects of having been victimised (Davis et al, 2020), the participants who had been personally victimised were 3.4 times as likely to report uncivil participation (H8) compared to those without such experiences.…”
Section: Discussionsupporting
confidence: 72%
“…Traditionally, problematic behaviour theory distinguishes the following three systems: the 'personality system' (including beliefs and attitudes); the 'environmental system' (including the 'social system,' such as one's peers or parents); the 'perceived environment' (i.e., the norms within that system); which all influence a forth system, namely the 'behaviour system,' which involves a covariation of different normtransgressing problematic behaviours. The theory has been developed and employed mostly in the context of (adolescent) norm-deviances (e.g., alcohol abuse as examined in Hays, Stacy, & di Matteo, 1987; for a review of the theories' application, see Jessor, 2017), but there is also scholarship arguing that problematic behaviour theory provides a useful perspective on online behaviour (De Leo & Wulfert, 2013;Lee, Kim, Hong, & Marsack-Topolewski, 2019).…”
Section: Problematic Behaviour Theory and Uncivil Participationmentioning
confidence: 99%
“…The relation between cyber peer victimization and aggression can be explained by the GST hypothesis, which assumes that children who experience adverse life events (e.g., peer victimization) are more likely to perpetrate bullying and violence as they age (Agnew, 1992). Targets of cyber aggression are inclined to experience strain and feel more stress and difficulty in normal peer interactions (Tian et al, 2018), which leads them to utilize poor coping strategies, such as aggressive behavior, to alleviate negative emotions or seek contact with deviant peers for approval (Lee et al, 2019; Ostrov, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to general strain theory (GST; Agnew, 1992), the experience of victimization is a source of interpersonal strain; victimized students may use aggressive behavior to mitigate undesirable feelings related to strain. A wealth of research also supports prospective relations between victimization and aggressive behavior (Jang et al, 2014; Lee et al, 2019). Therefore, in this study, we examined the heterogeneous co‐developmental patterns of physical, relational, and cyber aggression in elementary school children and further investigated the role of victimization experiences in the family and school settings in the heterogeneous co‐developmental patterns of physical, relational, and cyber aggression.…”
Section: Introductionmentioning
confidence: 88%
“…Some recent studies have found that gender might be a significant moderator in the relationship between deviant peer affiliation and adolescents’ problem behavior and risk-taking behavior in Chinese adolescents [ 39 , 43 ]. Bullying is closely related to external problem behaviors, and both are negative aspects of adolescent behavior development [ 46 , 47 , 48 ]. Based on this, we inferred that gender might also be a non-negligible moderator between deviant peer affiliation and adolescents’ bullying.…”
Section: Introductionmentioning
confidence: 99%